Retention Time Extended by Nanoparticles Improves the Eradication of Highly Antibiotic-Resistant Helicobacter pylori - Cheng-Jung Yao; Shu-Jyuan Yang; Chung-Huan Huang; Yuan-Ting Chang; Chung-Hao Wang; Ming-Jium Shieh; Tai-Horng Young (MDPI AG, 2022)
Helicobacter pylori infection usually causes gastrointestinal complications, including gastrointestinal bleeding or perforation, and serious infections may lead to gastric cancer. Amoxicillin is used to treat numerous bacterial infections but is easily decomposed in the gastric acid environment via the hydrolyzation of the β-lactam ring. In this study, we develop chitosan-based nanoparticles loaded with amoxicillin (CAANs) as an H. pylori eradication platform. The CAANs were biocompatible and could retain the antibiotic activity of amoxicillin against H. pylori growth. The mucoadhesive property of chitosan and alginate enabled the CAANs to adhere to the mucus layers and penetrate through these to release amoxicillin in the space between the layers and the gastric epithelium. The use of this nanoparticle could prolong the retention time and preserve the antibiotic activity of amoxicillin in the stomach and help enhance the eradication rate of H. pylori and reduce treatment time. These CAANs, therefore, show potential for the effective treatment of highly antibiotic-resistant H. pylori infection using amoxicillin.